Integrative Thematic Learning Model in Shaping Students' Character at Madrasah Ibtidaiyah Nurul Islam Lumajang - Sulthon, Elok Aini (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2024)
Learning plays an important role in achieving educational goals because the success of an education does not escape the role of learning itself. Good learning will produce a quality education and quality education is education that can shape the character of students because in essence education has two goals, namely helping humans to become capable, and helping humans to be better and have character. The integrative thematic learning model helps build student character, namely; Religious with habituation designed by the pesantren system which creates a generation of students with noble character. Responsibility for their duties Care for the environment by getting used to keeping the environment clean. This research uses a qualitative approach, descriptive qualitative method. Type of case study research. Purposive research subject technique. Observation, interview and documentation data collection techniques. Data analysis techniques using Miles and Huberman interactive analysis: collection, reduction, presentation of data and conclusion drawing/verification. Data validity using source and technique triangulation techniques. The results of these findings: 1) The connected integrative thematic learning model is in the form of planning (determining concepts and characters, formulating learning objectives, and learning steps). Implementation (arrangement of student places with a random system; learning applies 5M and the use of media as needed). Evaluation using process and results. 2) The spider web integrative thematic learning model in the form of planning (determining the central theme, identifying concepts and determining the schedule according to the theme), (delivery of objectives, demonstration, integrated practice, feedback, practice), evaluation using test and portfolio assessment.